2011
DOI: 10.1007/s12223-011-0032-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of Plesiomonas shigelloides as a possible zoonotic agent

Abstract: The most frequently used method for establishing epidemiological relationships between Plesiomonas shigelloides strains is O:H serotyping. However, a number of strains are not serotypeable and isolates from diverse sources can display the same serovar. Moreover, since the zoonotic nature of Plesiomonas has been suggested and this hypothesis is based on the identical serovars found in animals and humans, we intend to use four DNA-based techniques: random amplified polymorphic DNA-PCR, enterobacterial repetitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Plesiomonas has also been recovered from 3.9% to 7.4% of ring-billed and herring gull feces on bathing beaches located on southwestern Lake Michigan (71). Other avian species reported to yield P. shigelloides include whooper swan, black stork, goldeneyes, herons, and penguins (72,73,74).…”
Section: Invertebrate and Vertebrate Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plesiomonas has also been recovered from 3.9% to 7.4% of ring-billed and herring gull feces on bathing beaches located on southwestern Lake Michigan (71). Other avian species reported to yield P. shigelloides include whooper swan, black stork, goldeneyes, herons, and penguins (72,73,74).…”
Section: Invertebrate and Vertebrate Hostsmentioning
confidence: 99%
“…Detailed investigations of their relative frequencies in such hosts have not been published. These taxa include reptiles (alligator, lizard), cats, dogs, hares, red wolf, foxes, and a roach (42,72,74,75,76). Table 2 lists a compilation of animal species from which Plesiomonas has been recovered since 2000.…”
Section: Invertebrate and Vertebrate Hostsmentioning
confidence: 99%
“…and A. aquariorum [35,36] in the present study, which were decreased in the CHFM12/CSM group, are potentially harmful species in aquaculture. The recently described A. aquariorum is associated with a variety of human diseases [37], and Plesiomonas shigelloides, which is regarded as an emerging enteric pathogen, is also a possible zoonotic agent [38]. Our study showed that CHFM induced adaptation of the intestinal microbiota in tilapia and possibly prevented the intestinal tract from becoming colonized by potentially harmful species.…”
Section: Effects Of the Experimental Diets On The Population Of Adhesmentioning
confidence: 55%
“…Plesiomonas shigelloides, an emerging pathogen of humans and animals, is widespread in the aquatic environment. They have been isolated from various different animals, such as shellfish, freshwater fish, snakes, dogs, goats, cats, swine and monkeys (González-Rey et al, 2011). Interestingly, not all farmed fishes were infected with P. shigelloides, however, this bacterium is a common source of disease in grass carp, tilapia, Chinese giant salamander (Andrias davidianus) and black carp in China.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, P. shigelloides has been isolated from streams, lakes, estuarine waters, mammals, crustaceans, mollusks, reptiles, amphibians and fish (Alexander et al, 2016). P. shigelloides is an emerging enteric pathogen that is linked to intestinal and extra-intestinal infections in humans (González-Rey et al, 2011). It is recognized as a potential fish pathogen and has been isolated from red hybrid tilapia (Nadirah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%